Promoting Equity and Inclusion through Public Policy: Strategies for Addressing Systemic Discrimination and Inequality - Muh Syafril (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This study investigates methods for combating institutionalized racism and sexism through legislative action. As a means of fostering greater social mobility, the document begins by delineating policies that support education and training programs, financial aid, and social safety nets. Examining the policies and programs that have been effective in reducing inequality in our society, such as progressive taxation, minimum wage legislation, and healthcare access, the paper continues. The final section of the paper investigates programs promoting diversity and inclusion, affirmative action policies, and changes to enforcement practices, among other methods. Through the presentation of case studies of successful policies and programs, the ability of government involvement to create more equitable and inclusive societies is illustrated. The paper argues that eradicating institutionalized discrimination and prejudice throughout society is crucial for advancing toward equality and inclusion. By advocating for policies that support equity and inclusion, policymakers can help develop a more just and equitable society.